2003
DOI: 10.1128/jvi.77.2.1092-1104.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effect and Virus-Host Interactions in Response to Alpha Interferon, Gamma Interferon, Poly(I)-Poly(C), Tumor Necrosis Factor Alpha, and Ribavirin in Hepatitis C Virus Subgenomic Replicons

Abstract: The recently developed hepatitis C virus (HCV) subgenomic replicon system was utilized to evaluate the efficacy of several known antiviral agents. Cell lines that persistently maintained a genotype 1b replicon were selected. The replicon resident in each cell line had acquired adaptive mutations in the NS5A region that increased colony-forming efficiency, and some replicons had acquired NS3 mutations that alone did not enhance colony-forming efficiency but were synergistic with NS5A mutations. A replicon const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 70 publications
13
148
2
Order By: Relevance
“…This is further validated in vitro, in which treatment of cells harboring HCV replication with IFN-␣ results in a dosedependent decrease in HCV RNA. 19,20 Furthermore, long-term treatment of HCV replicon cells with IFN-␣ can "cure" these cells completely of HCV replication. 21 However, despite this, the complete spectrum of ISGs in the HCV-infected liver has not been identified, nor have the ISGs responsible for the control of HCV replication been defined.…”
Section: Discussionmentioning
confidence: 99%
“…This is further validated in vitro, in which treatment of cells harboring HCV replication with IFN-␣ results in a dosedependent decrease in HCV RNA. 19,20 Furthermore, long-term treatment of HCV replicon cells with IFN-␣ can "cure" these cells completely of HCV replication. 21 However, despite this, the complete spectrum of ISGs in the HCV-infected liver has not been identified, nor have the ISGs responsible for the control of HCV replication been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA prepared from liver and PBMC was used to perform microarray analyses 10,11 and quantitative reverse transcription polymerase chain reaction (RT-PCR; TaqMan) 19 as described in Supplemental Methods (Supplementary materials is available at the HEPATOLOGY website: http://interscience.wiley.com/jpages/0270-9139/ suppmat/index.html). Uninfected chimpanzees were inoculated subcutaneously with 5 million IU IFN-␣; blood and liver samples were obtained at 0, 4, 8, and 24 hours post-inoculation, followed by 30 days of rest before a second exposure to a different IFN-␣ (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although IP-10 was originally identified as an IFN-␥-specific transcript, its induction by IFN-␣ is well documented. 19 In contrast, MIG is still considered to be an IFN-␥-specific transcript and a sensitive marker for IFN-␥ function. 39 The current analysis demonstrated that MIG can be induced in hepatocytes by IFN-␣, although induction by IFN-␥ was 5-to 10-fold greater.…”
Section: Tissue-specific Responses To Ifn-␣mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies using HCV replication models, mutagenic effects of ribavirin have been identified by several 54,[56][57][58][59][60] but not all authors. 61 When infectivity was used as a functional readout for mutagenesis, diminished infectivity was found with ribavirin treatment of HCV cultures.58 , 60 The concentrations of ribavirin needed to achieve mutagenic effects were high (up to 400 uM) and may exceed those achieved in vivo.…”
Section: Ribavirin: Mechanism Of Action Clinical Insightsmentioning
confidence: 99%